2005
DOI: 10.1152/ajpendo.00405.2004
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a selective serotonin reuptake inhibitor with insulin in the control of hepatic glucose uptake in conscious dogs

Abstract: Whether hyperinsulinemia is required for stimulation of net hepatic glucose uptake (NHGU) by a selective serotonin reuptake inhibitor (SSRI) was examined in four groups of conscious 42-h-fasted dogs, using arteriovenous difference and tracer ([3-3 H]glucose) techniques. Experiments consisted of equilibration (Ϫ120 to Ϫ30 min), basal (Ϫ30 to 0 min), and experimental periods (Exp; 0 -240 min). During Exp, somatostatin, intraportal insulin [at basal (Ins groups) or 4-fold basal rates (INS groups)], basal intrapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Studies were carried out in conscious 42-h-fasted dogs of either sex (20 -23 kg). This length of fast in the canine does not induce hypoglycemia, raise the plasma levels of stress hormones, or exhaust liver glycogen (38,39). In addition, after a 42-h fast approximately two-thirds of hepatic glucose production is accounted for by gluconeogenic flux (48), comparable with overnight-fasted humans.…”
Section: Methodsmentioning
confidence: 99%
“…Studies were carried out in conscious 42-h-fasted dogs of either sex (20 -23 kg). This length of fast in the canine does not induce hypoglycemia, raise the plasma levels of stress hormones, or exhaust liver glycogen (38,39). In addition, after a 42-h fast approximately two-thirds of hepatic glucose production is accounted for by gluconeogenic flux (48), comparable with overnight-fasted humans.…”
Section: Methodsmentioning
confidence: 99%
“…Physiological studies by Moore and colleagues demonstrated increased hepatic glucose uptake after intraportal infusion of 5-HT or selective 5-HT uptake inhibitors [12][13][14][15]. This raised the question whether these effects are mediated by a direct effect of 5-HT on hepatocytes or by indirect mechanisms involving haemodynamic changes or altered transmission of afferent signals.…”
Section: Discussionmentioning
confidence: 99%
“…For the determination of phosphorylase a, the cells were extracted as described by Aiston et al [23] and phosphorylase a was assayed spectrometrically in the 13,000 g supernatant [15]; activity is expressed as mU/mg protein. For determination of glycogen synthase, cells were extracted and enzyme activity was determined radiochemically from the incorporation of UDP-[6-3 H]-glucose, as described by Aiston et al [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were conducted on twenty-one 42-h-fasted conscious mongrel dogs of either sex (18 -25 kg). This length of fast does not induce hypoglycemia, raise the plasma levels of stress hormones, or exhaust liver glycogen in the dog (42,43). Housing and diet have been described previously (21).…”
Section: Methodsmentioning
confidence: 96%